Occupational safety practices and implementation in primary schools, Perak, Malaysia - Subramaniam, Murugan; Baharudin, Mohd Rafee; Abdul Rahman, Anita; Muhamad Saliluddin, Suhainizam (IJISRT, 2022)
This study was carried out to assess the implementation of occupational safety and practices at all the primary schools in LMS district, Perak, Malaysia. Materials and Methods: A cross sectional study was carried at 102 schools (91.9% responsed) out of 111 schools in LMS district. A self-administered questionnaires form was used to ask about the safety knowledge, practices and implementation in the school. Results: The data analysis shows that overall occupational safety programmes and implementation are considered shallow. Safety coordinators knowledge on occupational safety legislation (75.5%) were poor due to less courses attended (80.4%). Even though safety programmes only focus on fire safety drill but majority of the respondent did not know how to use the fire extinguisher (62.7%). Many schools did not have fire exit signage (86.4%). Besides that, 76.5% of schools did not have qualified first aider. Almost half of the schools did not have any personnel protective equipment for pupil’s usage. Conclusion: As a conclusion, implementation and practices of occupational safety in all the primary schools are still lacking and need to be improved.